Hepatitis E Virus Infection in Immunosuppressed Patients: Natural History and Therapy - Kamar, Nassim; Rostaing, Lionel; Izopet, Jacques (Seminars in Liver Disease, 2013)
Interest in hepatitis E virus (HEV) infection has increased over the last few years since chronic HEV infection was first reported in transplant patients. Chronic genotype-3 HEV infections have been now reported in patients with a solid-organ transplant, hematology disease, and in those who are human immunodeficiency virus-positive. Cases of HEV-related cirrhosis have been also reported. Furthermore, HEV associated extrahepatic manifestations, including neurologic symptoms, kidney injuries, and hematological disorders, have been reported. Antiviral therapies, such as pegylated-interferon and ribavirin, have been found to be efficient in treating HEV infection. The aim of this review is to summarize the incidence, natural history, risk factors, and treatment of HEV infections in immunosuppressed patients. HEV-induced extrahepatic manifestations are described.
Keywords: hepatitis E virus; HEV; chronic infection; cirrhosis; ribavirin; extrahepatic symptoms